Paired Graphics: An Exploratory Study of Graphicacy - Boucheix, J.; Lowe, Richard; Ainsworth, S.; Betrancourt, M.; De Vries, E. (Universite Pierre-Mendes-France, 2012)
Adults viewed 37 varied paired graphics derived from school science textbooks and explained meaningful aspects of each item. Verbal responses and eye tracking results indicated that participants understood most of the items and directed their attention to high relevance aspects of the graphics. Although some variables,such as the typicality of the graphic pairs appeared to influence comprehension, others such as content complexity seemed to have no effect. The findings will be used as baseline data for current studies of children’s approaches to paired graphics and more formal investigations of the nature of graphicacy.